2017
DOI: 10.4236/ojss.2017.71001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tillage and Residue Retention on Soil Properties and Crop Yields in Wheat-Mungbean-Rice Crop Rotation under Subtropical Humid Climate

Abstract: The effects of conservation agriculture (CA) practices on soil properties along with crop yields of rice-based triple cropping systems have not been adequately assessed in Bangladesh. An experiment was conducted at Bangladesh Agricultural Research Institute, Gazipur, Bangladesh from 2009 to 2012 to assess the effects of tillage practices and crop residue retention on soil physical properties, soil organic carbon (SOC) and crop yields in a wheat-mungbeanrice system. Treatments consisted of three tillage practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
5
14
0
Order By: Relevance
“…Mahapatra (1990) found that one third of the inorganic N can be substituted by applying rice or wheat straw at the time of planting to give similar rice yields. Similar results were also reported by Salahin et al (2017); Sidhu and Beri (1988);Dhar et al (2014).…”
Section: Results and Discussion Plant Growth And Yieldsupporting
confidence: 89%
“…Mahapatra (1990) found that one third of the inorganic N can be substituted by applying rice or wheat straw at the time of planting to give similar rice yields. Similar results were also reported by Salahin et al (2017); Sidhu and Beri (1988);Dhar et al (2014).…”
Section: Results and Discussion Plant Growth And Yieldsupporting
confidence: 89%
“…Bhatt (2017) and Jat et al (2015) also found higher soil moisture content under ZT and MT, respectively, over CT. Residue retention improved soil moisture content at both the depths at podding, seed formation and at harvest as compared to NR (p < .05). These results corroborate the findings of Salahin et al (2017), who reported higher soil moisture content with residue retention. Greater surface cover by crop residues has been shown to enhance soil moisture content by increasing infiltration and reducing evaporation (Thierfelder & Wall, 2009).…”
Section: Soil Moisturesupporting
confidence: 92%
“…There is an improvement in numerous parameters of soil health (physical, chemical and biological quality) under conservation tillage by increasing carbon and nutrients concentration at the surface soil (Singh et al 2015; Salahin et al 2017). Advantages of zero tillage (ZT) after burning or removal of crop residues in the RWCS were reported in the IGP, particularly in NW India (Erenstein and Laxmi 2008).…”
Section: Introductionmentioning
confidence: 99%